2018
DOI: 10.3390/polym10111204
|View full text |Cite
|
Sign up to set email alerts
|

Role of Electrostatic Interactions on Supramolecular Organization in Calf-Thymus DNA Solutions under Flow

Abstract: Previous investigations were conducted on two concentrations of DNA solution: 4 mg/mL, for which it has been shown that no supramolecular organization is induced under flow at low shear rates; and 10 mg/mL, in which a liquid crystalline-type texture is formed under flow at low shear rates, attesting to an orientation of pre-organized chains. Rheological experiments are discussed and their results supported by small-angle X-ray scattering (SAXS) and flow birefringence visualization experiments. Scattering from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The radius of the cylinder core was fitted at R c = 0.8 ± 0.4 nm, whereas the thickness of the shell was found to be Δ S = 0.5 ± 0.4 nm. These values are in close agreement with reported values for DNA strands, with bases and phosphate groups forming the core of duplexes surrounded by a shell of hydration and counterion layers. , The cross-sectional radius ( R CS ) due to electrostatic repulsion between DNA chains was found to be R CS = 8.4 ± 1.1 nm, revealing average separation of about 16.8 nm between chains, in close agreement with previous data on calf-thymus DNA solutions …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The radius of the cylinder core was fitted at R c = 0.8 ± 0.4 nm, whereas the thickness of the shell was found to be Δ S = 0.5 ± 0.4 nm. These values are in close agreement with reported values for DNA strands, with bases and phosphate groups forming the core of duplexes surrounded by a shell of hydration and counterion layers. , The cross-sectional radius ( R CS ) due to electrostatic repulsion between DNA chains was found to be R CS = 8.4 ± 1.1 nm, revealing average separation of about 16.8 nm between chains, in close agreement with previous data on calf-thymus DNA solutions …”
Section: Resultssupporting
confidence: 91%
“…32,43 The cross-sectional radius (R CS ) due to electrostatic repulsion between DNA chains was found to be R CS = 8.4 ± 1.1 nm, revealing average separation of about 16.8 nm between chains, in close agreement with previous data on calf-thymus DNA solutions. 44 In the case of PNT/DNA complexes, the shape of the SAXS profiles is quite different, and data exhibit multiple structural levels across the q range investigated. By inspecting upper curves in Figure 1, we find out that the low q range is characterized by a power law decay scaling with exponents close to −4.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The viscosity is polyelectrolyte concentration dependent. At high polyelectrolyte concentrations, the viscosity is high due to the interconnectivity between chains from physical crosslinks between PESC aggregates (Figure 14) [128,132,134,135]. The solutions go from a viscoelastic fluid to more elastic as the phase becomes more gel-like [132,135].…”
Section: Outcomes Of Complexation-rheologymentioning
confidence: 99%
“…The sodium ion quenching experiment was used to further verify the interaction mode of compound 7a with DNA. Assuming that triazolyl PD 7a was mainly binding DNA with highly negatively charged through electrostatic interaction, increasing the concentration of the Na + ion could promote the interaction between Na + ion and DNA phosphate groups, change the charge distribution of DNA structure, and destroy the electrostatic interaction between DNA and the tested molecule, , thus causing a significant variation in the absorption of the DNA–compound system. As shown in Figure S4, the absorbance of the DNA– 7a complex exposed teeny change or just kept stable with increasing in contents of sodium chloride, which revealed that the electrostatic effect was not the main interaction.…”
Section: Resultsmentioning
confidence: 99%